A Pilot Study of the Effect of Sodium Thiosulfate on Urinary Lithogenicity and Associated Metabolic Acid Load in Non-Stone Formers and Stone Formers with Hypercalciuria - Okonkwo, Onyeka W. (Public Library of Science, 2013)
BACKGROUND AND OBJECTIVES: Sodium thiosulfate (STS) reduced calcium stone formation in both humans and genetic hypercalciuric stone forming (GHS) rats. We sought to measure urine chemistry changes resulting from STS administration in people. DESIGN, SETTING, PARTICIPANTS & MEASUREMENTS: STS was given to healthy and hypercalciuric stone forming adults. Five normal non-stone forming adults (mean age 33 years), and 5 people with idiopathic hypercalciuria and calcium kidney stones (mean age 66 years) participated. Two baseline 24-hour urine collections were performed on days 2 and 3 of 3 days of self-selected diets. Subjects then drank STS 10 mmol twice a day for 7 days and did urine collections while repeating the self-selected diet. Results were compared by non-parametric Wilcoxon signed rank test. The primary outcome was the resulting change in urine chemistry. RESULTS: STS administration did not cause a significant change in urinary calcium excretion in either group. In both groups, 24 hour urinary ammonium (P = 0.005) and sulfate excretion (P = 0.007) increased, and urinary pH fell (P = 0.005); citrate excretion fell (P<0.05) in hypercalciuric participants but not in non-stone formers. Among stone formers with hypercalciuria, 3 of 5 patients had measurement of serum HCO(3) concentration after the STS period: it did not change. The net effect was an increase in supersaturation of uric acid, and no change in supersaturation of calcium oxalate or calcium phosphate. CONCLUSIONS: The basis for studies demonstrating that STS prevented stones in rats and people was not reflected by the changes in urine chemistry reported here. Although serum HCO(3) did not change, urine tests suggested an acid load in both non-stone forming and hypercalciuric stone-forming participants. The long term safety of STS needs to be determined before the drug can be tested in humans for long-term prevention of stone recurrence.